The St. Ambrose School for Girls - Ward, Jessica, 1969- (Gallery Books, 2023)
"When Sarah Taylor arrives at the exclusive St. Ambrose School, she's carrying more baggage than just what fits in her suitcase. She knows she's not like the other girls-if the shabby, all-black, non-designer clothes don't give that away, the bottle of lithium hidden in her desk drawer sure does. St. Ambrose's queen bee, Greta Stanhope, picks Sarah as a target from day one-the most popular, powerful, horrible girl at school is relentless in making sure Sarah knows what the pecking order is. Thankfully, Sarah makes an ally out of her roommate Ellen "Strots" Strotsberry, a cigarette-huffing, devil-may-care athlete who takes no bullshit. Also down the hall is Nick Hollis, the devastatingly handsome RA, and the object of more than one St. Ambrose student's fantasies. Between Strots and Nick, Sarah hopes she can make it through the semester, dealing with not only her schoolwork and a recent bipolar diagnosis, but Greta's increasingly malicious pranks. Sarah is determined not to give Greta the satisfaction of breaking her. But when scandal unfolds, and someone ends up dead, her world threatens to unravel in ways she could never have imagined. THE ST. AMBROSE SCHOOL FOR GIRLS is a dangerous, delicious, twisty coming-of-age tale that will stay with you long after you turn the last page"--